The U.S. health care system’s uneasy relationship with primary care (Italian Journal of Public Health, 2010)
Background: The main purpose of this essay is to review the role of primary care in the U.S. health caresystem and assess the probability that health reform will lead to greater emphasis on primary care.Methods: The author conducted a literature review to present an historical analysis of policies designed toincrease the availability and use of primary care in the U.S.Results: Despite widespread agreement that the use of primary care should be expanded, U.S. policies haveencouraged the growth of a system that relies predominantly on specialty care. The 2010 health reformlaw includes several provisions designed to increase the availability and use of primary care, but the newCongress has threatened to delay the law’s implementation.Conclusions: As concepts, primary care and prevention enjoy nearly universal support in the U.S., but thereality does not match the rhetoric.
Keywords: primary care; prevention; patient protection and affordable care act; managed care